2004
DOI: 10.2337/diabetes.53.2.474
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Type 2 Diabetes in Alzheimer Disease

Abstract: Alzheimer disease and type 2 diabetes are characterized by increased prevalence with aging, a genetic predisposition, and comparable pathological features in the islet and brain (amyloid derived from amyloid ␤ protein in the brain in Alzheimer disease and islet amyloid derived from islet amyloid polypeptide in the pancreas in type 2 diabetes). Evidence is growing to link precursors of amyloid deposition in the brain and pancreas with the pathogenesis of Alzheimer disease and type 2 diabetes, respectively. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
595
0
14

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 831 publications
(622 citation statements)
references
References 76 publications
13
595
0
14
Order By: Relevance
“…A great deal of interest has been drawn to the role of insulin signaling in the etiology and pathogenesis of AD (54,55). Not only is the type 2 diabetes mellitus a risk factor for AD (56,57), but these two diseases also share several common molecular pathological features such as amyloidogenesis (1, 58 -60) and insulin resistance (54,60,61). Here we show that cultured nerve cells possess a capacity of degrading exogenously added ADDLs in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 88%
“…A great deal of interest has been drawn to the role of insulin signaling in the etiology and pathogenesis of AD (54,55). Not only is the type 2 diabetes mellitus a risk factor for AD (56,57), but these two diseases also share several common molecular pathological features such as amyloidogenesis (1, 58 -60) and insulin resistance (54,60,61). Here we show that cultured nerve cells possess a capacity of degrading exogenously added ADDLs in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 88%
“…There may be shared predisposition for developing islet amyloid in patients with diabetes and brain amyloid in those with Alzheimer's disease. A population-based clinicopathological study has shown the possible link between neurodegenerative processes that lead to loss of cortical brain cells in Alzheimer's disease and the loss of beta cells in type 2 diabetes [50].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and Alzheimer disease are risk factors for each other, and it is possible that these two diseases may share common molecular defects (46,47). The Alzheimer disease genes, presenilin-1 and presenilin-2, are key mediators in neurodegeneration (20,47) but their role in ␤-cell degeneration remains unclear.…”
Section: Discussionmentioning
confidence: 99%